Strategic Lawsuits against Public Participation in the European Union: The Anti-SLAPP Directive - Cuartero Rubio, Mª Victoria (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The European Union has taken an essential step in the fight against strategic lawsuits against public participation and in the defense of freedom of expression and information, democracy and the rule of law with the adoption of the Anti-SLAPP Directive. A highly topical matter of the utmost interest, this paper makes a critical reading of the main lines of the European Directive and points out some aspects that remain open. The analysis pays close attention to the evolution of the European Directive as of its proposal up to its final text: an essential information for its correct transposition and future interpretation and application.